Penerapan Program BLT Sebagai Bentuk Pemenuhan Hak Masyarakat Miskin di Indonesia - Syah, Aurelia Zerikha; Sachmaso, Hana Humaira; Fadillah, Fatma Putri; Ardiana, Oktavia Dwi; Narindra, Rochella Amalia; Yuli W, Yuliana (Media Hukum Indonesia (MHI), 2024)
The BLT Program is a government effort to reduce poverty levels and improve social welfare by providing financial assistance to economically disadvantaged and vulnerable families. This study aims to assess the effectiveness of implementing the BLT Program in achieving these objectives, as well as to explore the correlation between this policy and Indonesia's legal framework in the context of achieving Sustainable Development Goal (SDG) No. 16, which pertains to peace, justice, and institutional strengthening. The method used is a literature review with a descriptive analytical approach, examining secondary data from various reliable sources. Findings from this research indicate that while BLT helps alleviate the burden on impoverished communities, there are challenges in its implementation, including delays in distribution and inaccuracies in target determination. To optimize the benefits of BLT, improvements in distribution mechanisms, inter-agency coordination, and stricter monitoring are necessary.